Analisis Persetujuan Berusaha PT Ratu Samban Mining Bengkulu Tinjauan dari Hukum Tata Ruang - Muhammad Adrian Fitra Yamazaki; Aldo Kurniawan; Adib Kumara Reisman; Fadel Jovinka; Edra Satmaidi (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study aims to analyze the legal validity of the Business Approval of PT Ratu Samban Mining (RSM) from the perspective of Law Number 26 of 2007 on Spatial Planning. This research employs a normative legal method using statutory and case approaches. The findings indicate that although PT RSM formally possesses a mining business permit, substantively there are indications of non-compliance with the Regional Spatial Plan (RTRW), particularly concerning alleged operations in protected areas and the low post-mining reclamation rate of only 28.57%. Such inconsistencies may render the business approval legally void as stipulated in Article 37 paragraph (7) of the Spatial Planning Law. The legal implications include administrative sanctions, criminal liability, and obligations to restore spatial functions. Furthermore, the study identifies structural weaknesses in spatial planning supervision, including inadequate field verification and lack of institutional coordination. Therefore, strengthening supervision mechanisms, conducting periodic spatial audits, and improving policy harmonization are essential to ensure sustainable spatial utilization.